Application of iron sulfide particles for groundwater and soil remediation: A review. (1st February 2016) - Gong, Yanyan; Tang, Jingchun; Zhao, Dongye
Abstract: Rapid industrialization and urbanization have resulted in elevated concentrations of hazardous inorganic and organic contaminants in groundwater and soil, which has become a paramount concern to the environment and the public health. In recent years, iron sulfide (FeS), a major constituent of acid-volatile sulfides, has elicited extensive interests in environmental remediation due to its ubiquitous presence and high treatment efficiency in anoxic environment. This paper provides a comprehensive review on recent advances in: (1) synthesis of FeS particles (including nanoscale FeS); and (2) reactivity of FeS towards a variety of common environmental contaminants in groundwater and soil over extended periods of time, namely, heavy metals (Hg(II), Cu(II), Pb(II), and Cr(VI)), oxyanions (arsenite, arsenate, selenite, and selenate), radionuclides (e.g., uranium (U) and neptunium (Np)), chlorinated organic compounds (e.g., trichloroethane, trichloroethylene, and p -chloroaniline), nitroaromatic compounds, and polychlorinated biphenyls. Different physiochemical and biological methods for preparing FeS with desired particle size, structure, and surface properties are discussed. Reaction principles and removal effectiveness/constraints are discussed in details. Special attention is placed to the application of nanoscale FeS particles because of their unique properties, such as small particle size, large specific surface area, high surface reactivity, and soil deliverability in the subsurface. Moreover, current knowledge gaps and further research needs are identified. Graphical abstract: Highlights: Overviewed latest development in synthesizing FeS particles for environmental uses. Examined removal/immobilization of heavy metals and radionuclides by FeS particles. Critically reviewed reductive transformation of contaminants by FeS particles. Elucidated reaction mechanisms governing removal or transformation of contaminants. Identified critical knowledge gaps and future research needs on FeS applications.